Feigning Acute Intermittent Porphyria. (25th November 2014) - Elkhatib, Rania; Idowu, Modupe; Brown, Gregory S.; Jaber, Yasmeen M.; Reid, Matthew B.; Person, Cheryl
Abstract : Acute intermittent porphyria (AIP) is an autosomal dominant genetic defect in heme synthesis. Patients with this illness can have episodic life-threatening attacks characterized by abdominal pain, neurological deficits, and psychiatric symptoms. Feigning this illness has not been reported in the English language literature to date. Here, we report on a patient who presented to the hospital with an acute attack of porphyria requesting opiates. Diligent assessment of extensive prior treatment records revealed thirteen negative tests for AIP.